2019
DOI: 10.1111/acps.13036
|View full text |Cite
|
Sign up to set email alerts
|

Internalizing and externalizing symptoms and suicidal behaviour in young people: a systematic review and meta‐analysis of longitudinal studies

Abstract: Internalizing and externalizing symptoms and suicidal behaviour in young people: a systematic review and meta-analysis of longitudinal studies.Objective: To assess internalizing and externalizing symptoms as risk factors for suicidal behaviour and suicide among adolescents and young adults. Method: We conducted a systematic review of articles published until January 2017. We identified 26 883 potential papers; 1701 full-text articles were assessed for eligibility, of which 1479 were excluded because of methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 82 publications
4
40
0
2
Order By: Relevance
“…However, it has been found that anxious-depressive symptoms mediate between COVID-19 fear and life satisfaction (Satici, Gocet-Tekin, Deniz & Satici, 2020a) and that positive factors may protect against suicidal ideation (Chang et al, 2017;Sánchez-Alvarez et al, 2020). As regards the relationship between anxious-depressive symptoms and suicide ideation, previous studies have shown this to be a positive relationship (Blasco et al, 2018;Soto-Sanz et al, 2019). Fear of COVID-19 has previously been associated with depression and anxiety symptoms as a statistically significant variable (Fitzpatrick et al, 2020;Harper et al, 2020;Satici et al, 2020a).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, it has been found that anxious-depressive symptoms mediate between COVID-19 fear and life satisfaction (Satici, Gocet-Tekin, Deniz & Satici, 2020a) and that positive factors may protect against suicidal ideation (Chang et al, 2017;Sánchez-Alvarez et al, 2020). As regards the relationship between anxious-depressive symptoms and suicide ideation, previous studies have shown this to be a positive relationship (Blasco et al, 2018;Soto-Sanz et al, 2019). Fear of COVID-19 has previously been associated with depression and anxiety symptoms as a statistically significant variable (Fitzpatrick et al, 2020;Harper et al, 2020;Satici et al, 2020a).…”
Section: Resultsmentioning
confidence: 95%
“…This increase in anxious-depressive symptoms can cause serious repercussions. In previous studies, the occurrence of anxiety and depressive disorders, or the presence of symptoms, has been associated with suicidal behavior (Gili et al, 2019;Gilmour, 2016;Sareen et al, 2005;Soto-Sanz et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Three thought‐stimulating research reports are published in this issue of ‘Acta Psychiatrica Scandinavica’ (). These three papers demonstrate innovative approaches to the studies of suicidal behavior.…”
mentioning
confidence: 99%
“…Soto‐Sanz et al. performed a systematic review and meta‐analysis of longitudinal studies of a relation between internalizing and externalizing symptoms and suicidal behavior in young (12–26 y.o.) people.…”
mentioning
confidence: 99%